Gambaran Sitologi Cairan Peritoneal dan Sinovial Itik Bali (CYTOLOGIC FIGURES OF PERITONEAL AND SYNOVIAL FLUIDS IN BALI DUCKS) - Utama, Iwan Harjono; Widyastuti, Sri Kayati; Adi, Anak Agung Ayu Mirah; Erawan, I Gusti Made Krisna; Winaya, Ida Bagus Oka; Ardana, Ida Bagus Komang; Rasid, Achoiro Wati; Yoga, Tyas Pandieka (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
This study aim was to observe cellular composition and morphology in peritoneal and synovial fluids ofbali ducks. This study used 50 ducks, which were composed of 21 males and 29 females aged 8 to 12 weeks.After being declared clinically healthy, the sample ducks were slaughtered and peritoneal fluid specimenfrom the abdominal cavity and the synovial fluid of joints tibiotarsal were collected. Then, in preparationfor the specimen, each of fluid was smeared and stained with Giemsa. Observations were made under amicroscope with a magnification of 1000 times and observations expressed in the average number of cellsper field of view observation. The results showed (duck population that most of the observed sample): inthe peritoneal fluid there was 36% eosinophils observed and 38% had heterophile cells with 0-3 cells perfield of magnification 1000x view. Similarly, 28% ducks had lymphocytes with 13-16 cells, and as much as28% of ducks had macrophage cells with 5- 8 cells in observation . In the synovial fluid, however, 64%sample ducks had monocytes, while 72% having lymphocytes with 1-18 cells each of view field withmagnification 1000x. In addition, in the synovial fluid, as much as 62% of ducks also observed had 1 to 3cells heterophiles and 60% ducks had eosinophils (polimorphonuclear cells) per view field observation.Macrophage cells that were found in the peritoneal fluid were mainly hyper granulated. It can be concludedthat the amount of mononuclear cells in both types of body fluids is likely more dominant compared to thenumber of polymorphonuclear cells.
Keywords: cytology, peritoneal fluid, synovial fluid, bali ducks